As an Ottoman Teacher and Engineer: Mustafa Salim Bey and His Work Titled as Hesâb-ı Asgar-ı Nâmütenâhiyat (Kısm-ı Evvel) Hesâb-ı Tefâzülî - Ayşe KÖKCÜ (Ankara Üniversitesi Dil ve Tarih-Coğrafya Fakültesi Dergisi, 2017)
In this article, we will look at the life of Mustafa Salim Bey, who was a teacher and an engineer having grown up during the Ottoman period and his work, called as Hesâb-ı Asgar-ı Nâmütenâhiyat (Kısm-ı Evvel) Hesâb-ı Tefâzülî. He gave lectures on differential and integral calculations, high algebra, technical mechanic and mathematical mechanic at Hendese-i Mülkiye-i Şâhâne, Darul Funun (House of Sciences) and Darüşşafaka, which were outstanding schools of the time. Mustafa Salim Bey wrote his work, called as Hesâb-ı Asgar-ı Nâmütenâhiyat, as a resource book for students at Hendese-i Mülkiye-i Şâhâne (Civilian School of Engineering). However, the book was not limited only to Hendese-i Mülkiye-i Şâhâne and then it was probably used as a course book at War School and Darul Funun as well. Mentioning differential calculation, the work is very significant in terms of the subjects which it contains, such as quaternion calculation, partial differential equations. As far as we have ascertained, of all the books on differential calculation during the Ottoman Period this is the first work to have mentioned such subjects.